Case Report: Theory of Mind and Figurative Language in a Child With Agenesis of the Corpus Callosum - Melogno, Sergio; Pinto, Maria Antonietta; Scalisi, Teresa Gloria; Badolato, Fausto; Parisi, Pasquale (Frontiers in Psychology, 2021)
In this case report we studied Theory of Mind (ToM) and figurative language comprehension in a 7.2 year-old child, conventionally named RJ, with isolated and complete Agenesis of the Corpus Callosum (ACC), a rare malformation due to the absence of the Corpus Callosum, the major tract connecting the two brain hemispheres. To study ToM, which is the capability to infer the other’s mental states, we used the classical false belief tasks, and to study figurative language, i.e. those linguistic usages involving non literal meanings, we used tasks assessing metaphor and idiom comprehension. RJ’s intellectual level, and his phonological, lexical and grammatical abilities were all adequate. In both ToM false belief tasks and novel sensory metaphor comprehension, RJ showed a delay of three years, and a significant gap compared to a typically developing control group while in idioms his performance was at the border of average. These outcomes suggest that RJ has a specific pragmatic difficulty in all tasks where he must interpret the other’s communicative intention, as in ToM tasks and novel sensory metaphor comprehension. The outcomes also open up interesting insights into the relationships between ToM and figurative language in children with isolated and complete ACC.